Effect of Aphid infestation on the Biochemical Constituents of Mustard (Brassica juncea) plant - Vijay Kumar Sinhal2, Pushpa Singh1* and (Journal of Phytology, 2011)
Mainly two aphid species viz., Lipaphis erysimi (Kalt) and Myzus persicae (Sulzer) were recorded on mustard crop. The infestation of insect pests caused considerable damage to the individual parts (leaf, stem, inflorescence and seeds) of the crop plants and significantly reduced the nutritional constituents (lipid, carbohydrate, nitrogen and protein levels) of mustard plants at different growth stages. Lipaphis erysimi was found to be the most active pest of mustard. These aphids have appeared in the fields especially with the onset of flowering. The loss in biochemical nutritive of plant foliage due to aphid infestation would degrade the quality of the products made of from different parts of mustard crop.